2015
DOI: 10.11118/201563062127
|View full text |Cite
|
Sign up to set email alerts
|

Tax Shift by Economic Functions and Its Effect on Economic Growth in the European Union

Abstract: The aim of the paper is to examine eff ects of tax shi on economic growth and provide a direct empirical evidence in the European Union (EU). It is used the Eurostat's defi nition to categorize tax burden by economic functions and implicit tax rates of consumption, labour and capital are investigated. First, paper summarizes main development of tax shi in a whole EU till 2014 and followed empirical analysis is based on annual panel data of 22 EU Member States in years 1995-2012 (time span is divided into a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Also, Widmalm (2001) found empirical evidence that the tax progressivity may be associated with low economic growth. The impact of certain taxation elements was also found by several authors such as Stoilova & Patonov (2012) and Szarowská (2013).…”
Section: Literature Reviewsupporting
confidence: 68%
“…Also, Widmalm (2001) found empirical evidence that the tax progressivity may be associated with low economic growth. The impact of certain taxation elements was also found by several authors such as Stoilova & Patonov (2012) and Szarowská (2013).…”
Section: Literature Reviewsupporting
confidence: 68%
“…Kalaš et al (2017) confirmed a significant correlation between taxes and economic growth in Serbia meausred by gross domestic product growth rate. Szarowska (2013) identified significant and positive implications of indirect taxes on gross domsetic product growth rate in European Union for the period 1995-2010. Bajo-Rubion and Gomez-Plana (2015 identified that growth of direct taxes had a negative effect on gross domestic product and employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We often come across the statements that have only theoretical basis without generally valid empirical evidence. Economic models are largely based on the argument that the yield curve tends to be flatter in the situation of the tight monetary policy and the economic slowdown typically occurs with a slight time lag (Szarowska, 2015).…”
mentioning
confidence: 99%